Peran Generasi Muda dan Partisipasi Dalam Pemilihan Kepala Desa di Kecamatan Percut Seituan Kota Medan - Ardawani Hutasoit; Fani Nolpiana Nadapdap; Grace Michael Sihombing; Halking (CV Putra Publisher, 2025)
This research aims to analyze the role of the younger generation and their participation in the election of village heads in Percut Sei Tuan District, Medan City. The younger generation has great potential in determining the direction of village development through their active participation in local level democratic processes. However, there are still challenges in encouraging political awareness and the interest of the younger generation to participate. This research method uses a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the role of the younger generation in village head elections still needs to be improved, especially in the aspects of political understanding, awareness of the importance of their votes, and the initiative to get involved in various campaign activities. This research suggests that there should be more intensive political education and socialization programs so that the younger generation is more motivated to actively participate in village head elections, so that they can contribute to better village development. In analyzing how the younger generation plays a role in the process of selecting Village Heads in Percut Seituan District, Medan City. The younger generation has great potential in supporting social and political development, especially in increasing political involvement at the village level. Even so, the participation of the younger generation in the Village Head Election in Percut Seituan District is still inadequate. This occurs due to many factors, such as a lack of political awareness, minimal information about the electoral process, and limited opportunities for the younger generation to be actively involved in local politics. This research applies a qualitative approach by conducting in-depth interviews with a number of young people, village head candidates and community leaders. Research reveals that the young generation in Percut Seituan District has a great opportunity to be involved in village head elections. However, they are faced with major obstacles, namely a lack of adequate political knowledge and an apathetic attitude towards local politics. Therefore, steps need to be taken to increase political awareness among the younger generation and provide wider opportunities for them to be involved in the democratic process in the village. The active involvement of the younger generation in village head elections will increase democracy at the local level and encourage the formation of village governments that are more responsive to the needs of residents.